Predictive Power of Adherence to Nurses\' Care Behaviors from Patients\' Perspectives by Nurses\' Professional Commitment - Parivash KARIMI; Farzin MOLLAZADEH; Hossein HABIBZADEH; Madineh JASEMI (Shahid Sadoughi University of Medical Sciences, 2022)
Introduction: Optimal nursing care is an important indicator of the quality and effectiveness of the health care system and is associated with professional commitment. This study aims to investigate the predictive power of adherence to nurses' care behaviors from patients' perspectives by nurses' professional commitment working in Urmia educational hospitals in 2018-2019. Methods: This descriptive-cross sectional study was conducted on 100 nurses working in educational hospitals affiliated to Urmia University of Medical Sciences in 2018-2019 who were selected by stratified random sampling. Demographic information questionnaire, nurses' professional commitment questionnaire (NPCS), and nurses' caring behavior inventory (CBI) were used for data collection. The data were analyzed by SPSS 16 software using descriptive and inferential statistical methods, correlation and stepwise regression. Results: The results of this study showed that there is a direct relationship between professional commitment and adherence to caring behaviors (r = 0.31 and p = 0.02). Moreover, dimensions of nurses 'professional commitment (perception of nursing, satisfaction with the nursing profession, getting involved with the nursing profession, and self-sacrifice for the nursing profession) account for 26% of the variance in adherence to nursing care behaviors. The dimension of nurses' professional commitment has the most significant effect after self-sacrifice for the nursing profession (P = 0.029, B = 0.30). Conclusion: Considering the role of professional commitment on the level of adherence to nurses' caring behaviors, it is essential to recognize the factors affecting nurses' professional commitment and make comprehensive planning to enhance the professional commitment of nurses.